HpaP, a novel regulatory protein with ATPase and phosphatase activity, contributes to full virulence in Xanthomonas campestris pv. campestris - Ping Cui; Rui‐Fang Li; Da‐Pei Zhang; Ji‐Liang Tang; Guang‐Tao Lu (Environmental Microbiology, 2018)
Summary The ability of the bacterial phytopathogen Xanthomonas campestris pv. campestris ( Xcc ) to cause disease is dependent on the type III secretion system (T3SS). Proteins of the Xcc T3SS are encoded by hrp (hypersensitive response and pathogenicity) genes and whose expression is mainly controlled by the regulators HrpG and HrpX. Here, we describe the identification and characterization of a previously unknown regulatory protein ( named HpaP), which plays important role in hrp gene expression and virulence in Xcc . Clean deletion of hpaP demonstrated reduced virulence and HR (hypersensitive response) induction of Xcc and alterations in cell motility and stress tolerance. Global transcriptome analyses revealed that most hrp genes were down regulated in the hpaP mutant, suggesting HpaP positively regulates hrp genes. GUS activity assays implied that HpaP regulates the expression of hrp genes via controlling the expression of hrpX . Biochemical analyses revealed that HpaP protein had both ATPase and phosphatase activity. While further site‐directed mutagenesis of conserved residues in the PTP loop (a protein tyrosine phosphatase signature) of HpaP resulted in the loss of both phosphatase activity and regulatory activity in virulence and HR. Taken together, the findings identify a new regulatory protein that controls hrp gene expression and virulence in Xcc .